2014
DOI: 10.1890/130145
|View full text |Cite
|
Sign up to set email alerts
|

Amphibians in the climate vise: loss and restoration of resilience of montane wetland ecosystems in the western US

Abstract: Wetlands in the remote mountains of the western US have undergone two massive ecological “experiments” spanning the 20th century. Beginning in the late 1800s and expanding after World War II, fish and wildlife managers intentionally introduced millions of predatory trout (primarily Oncorhynchus spp) into fishless mountain ponds and lakes across the western states. These new top predators, which now occupy 95% of large mountain lakes, have limited the habitat distributions of native frogs, salamanders, and wetl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 56 publications
(132 reference statements)
4
68
0
Order By: Relevance
“…This assumption was supported by concurrent dip‐netting efforts and surveys of anuran calls, which found similar trends in species composition (J. D. Holbrook, A. P. Berman, and D. Filipiak, unpublished). Although this was an observational study, the evidence for predatory impacts of fish on aquatic amphibians is supported by experiments (Smith et al ., ; Baber & Babbitt, ), observations of fish introductions (Segev et al ., ) and other observational studies (Skelly, ; Babbitt & Tanner, ; Ryan et al ., ). The community‐level differences observed in our wetlands suggested that all anurans were sensitive to fish to some extent.…”
Section: Discussionsupporting
confidence: 63%
“…This assumption was supported by concurrent dip‐netting efforts and surveys of anuran calls, which found similar trends in species composition (J. D. Holbrook, A. P. Berman, and D. Filipiak, unpublished). Although this was an observational study, the evidence for predatory impacts of fish on aquatic amphibians is supported by experiments (Smith et al ., ; Baber & Babbitt, ), observations of fish introductions (Segev et al ., ) and other observational studies (Skelly, ; Babbitt & Tanner, ; Ryan et al ., ). The community‐level differences observed in our wetlands suggested that all anurans were sensitive to fish to some extent.…”
Section: Discussionsupporting
confidence: 63%
“…Frequent dry conditions and the absence of persistent surface connectivity can preclude fish population establishment or recruitment after extirpation (35,125). Fish preclusion has implications for survival of juvenile amphibian, crustacean, and insect fauna (32,(126)(127)(128), many of which disperse as adults to upland habitats or downstream water bodies. Indeed, models predict that loss of GIW habitats would impact a wide array of fauna, not just permanent residents, and most prominently, turtles, amphibians, birds, and small mammals (36), many of which are imperiled (38).…”
Section: Fig 2 Across Blocks (A-h Maps Inmentioning
confidence: 99%
“…zero recruitment (Arntzen and Teunis 1993;Griffiths andWilliams 2000, 2001;Ryan et al 2014). Pond desiccation may also be beneficial to amphibians as it can periodically eliminate predators (Adams 2000;Ryan et al 2014). However, irrespective of predation pressure, desiccation before the juveniles are ready to leave the pond is detrimental for recruitment.…”
Section: Pond Desiccationmentioning
confidence: 99%
“…However, irrespective of predation pressure, desiccation before the juveniles are ready to leave the pond is detrimental for recruitment. It is this effect of early desiccation on recruitment, which can be enhanced by climate change as shown by Ryan et al (2014), that is relevant to consider here. The probability of pond desiccation was assumed to depend on a combination of the accumulated water deficit, and the ground water level at the pond's location.…”
Section: Pond Desiccationmentioning
confidence: 99%